On the chemical reactions of carbon dioxide isoelectronic molecules CS2 and OCS with 1-butyl-3-methylimidazolium acetate - Isabel Cabaco, M.
Raman and NMR spectroscopies show that CS2 and OCS react spontaneously with 1-butyl-3-methylimidazolium acetate [C(4)mim] [Ac] in the liquid phase. The formation of [C(4)mim] CO2, [C(4)mim] COS, CH3COS- and gaseous CO2 and OCS in both systems demonstrates that the anion plays an unexpected role not observed in the CO2-[C(4)mim] [Ac] reaction.